710 The impact of comorbidities on the physical and psychological dimension in heart failure patients (Balneo and PRM Research Journal, 2024)
Assessing patients' quality of life is frequently used in medical research. Patients di-agnosed with heart failure (HF) have reduced exercise tolerance and reduced quality of life due to reduced heart pump function. The objectives of the study are (i) to assess quality of life and comorbidities in HF patients; (ii) to compare quality of life in the physical and psychological do-mains according to drug treatment followed and (iii) to identify predictors of the two domains as-sessed. Methods. A cross-sectional study was conducted between February 2023 and May 2024. A total of 169 patients with HF were included and were distributed into two groups: the HF -S/V group (N=64) who received treatment with sacubitril/valsartan and the HF -CT group (N=105) received treatment with conventional therapy. Two questionnaires were used to assess patients: the World Health Organization's Quality of Life Questionnaire (WHOQOL-BREF) questionnaire and the Charlson Comorbidity Index (CCI). Results: The values determined for physical and psy-chological health were significantly lower for Group HF - S/V (51.391 ± 22.232 vs. 61.79 ± 20.04, p=0.002, respectively 59.203 ± 16.871 vs. 64.933 ± 17.448, p=0.038). Approximately 25% of all re-cruited patients distributed in the 2nd CCI category (CCI score 3-4) have an overall poor and moderately poor perception of quality of life vs. 35.5% of patients distributed in the 3rd CCI cate-gory (CCI ≤ 5); 55% of them belong to the HF - S/V group. A good perception of health status is held by 29 (17.16% of the HF group) of the patients distributed in the 2nd CCI category and 28 (16.56%) have a low and moderate perception. Conclusions: The values for the Physical health domain are moderately low, while the values obtained for the psychological domain show that this domain is less affected. Predictors identified for physical health and psychological well-being are patient age, weight, CCI.